A Review on Ahara with special reference to body organs - Prajapat, Monika; Sharma, Ashok Kumar; Sharma, Kishori Lal; Meena, Rekhraj; Nigam, Ayushi (International Research Journal of Ayurveda & Yoga, 2023)
According to Ayurveda, all living and non living objects in the universe are made up of Panchamahabhutas. In accordance with the requirements of Loka Purusha Samaya Siddhanta1, the world and the human body are connected entities with the same panchabhuta constitution. Finding things that behave or look like organs and figuring out which foods are ideal for a certain organ or organ system both use the same notion. Caraka Samhita describes three supports of life viz. ahara (intake of food), nidra (sleep) and bramhacarya (control of senses and spiritual bliss conducive to the knowledge of Bramhan). Food (ahara) is regarded as the most significant of these. Hitakara/pathya diet promotes longevity, strength, intelligence, a clear voice, and a healthy complexion in addition to maintaining good health. Organs should be kept healthy to improve our overall quality of life. Different diet products are mentioned for various organs to keep them healthy and disease free. Various pathya ahara are being mentioned here for specific organs which is to be followed by everyone along with proper Dinacharya and Ritucharya accordingly.